2007
DOI: 10.1038/sj.onc.1210782
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitotic exit by the RNF8 ubiquitin ligase

Abstract: RNF8 is a ubiquitin ligase with a FHA domain near its N terminus, and a RING-finger domain at its C terminus, through which it recruits several ubiquitin-conjugating enzymes. In metazoans, only the mitotic checkpoint regulator CHFR shares this domain architecture. Here we show that RNF8 is a nuclear protein that follows a cellcycle-dependent turnover, reaching its highest levels in mitosis, followed by a strong decline in late mitotic stages. Overexpression of RNF8 caused a delay in cytokinesis and the frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 28 publications
6
35
0
1
Order By: Relevance
“…These effects are consistent with delayed and abortive cytokinesis. [36][37][38] Overall, the number of midbodies in Nup153-depleted cells was twice that of control cells (Fig. 7F).…”
Section: Resultsmentioning
confidence: 95%
“…These effects are consistent with delayed and abortive cytokinesis. [36][37][38] Overall, the number of midbodies in Nup153-depleted cells was twice that of control cells (Fig. 7F).…”
Section: Resultsmentioning
confidence: 95%
“…6D), as reported for their S. pombe counterparts (10). We further note that, while this article was under review, another group also reported that DMA1/RNF8 regulates mitotic exit (23). Interestingly, depletion of DMA1/RNF8 compromised the ability of nocodazole-treated cells to maintain mitotic arrest in prometaphase/metaphase, although the MEN, which is inhibited by DMA1/RNF8, is thought to be activated later in mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…35 Our discovery that RNF8 is involved in PCNA ubiquitination now extends its potential functions into the DDT pathway. The latter is an S-phase checkpoint response that is activated by DNA damage caused by UV and other genotoxic agents.…”
Section: Discussionmentioning
confidence: 99%